Innervation in tissue engineered corneal equivalents - Suuronen, Erik (University of Ottawa (Canada), 2004)
A sensory nerve supply is crucial for optimal function of the cornea. However, the mechanisms for successful innervation and the signalling pathways between nerves and their target tissue are not fully understood. Engineered tissue substitutes can provide controllable environments in which to study tissue innervation. I have therefore engineered human corneal substitutes that promote nerve in-growth in a pattern similar to in vivo re-innervation. The methodology developed for the fabrication of such an innervated model cornea and for subsequent investigation of the function of these nerves is discussed in this thesis. Briefly, nerve in-growth into the tissue-engineered cornea is enhanced by the addition of laminin and nerve growth factor, but not retinoic acid. I demonstrated that these nerves are morphologically equivalent to natural corneal nerves and make appropriate contact with their target cells, which consequently, were found to be required for their survival. The nerves had functional sodium channels and generated action potentials similar to those of native nerve endings. I also demonstrated that the nerves could respond appropriately to chemical and physical stimuli and play an important role in the overall functioning of the bioengineered tissue. The presence of nerves conferred some protection to the epithelium from chemical insult and differential retention of sodium was observed within the nerve fibres themselves. As such, this model could be further developed for use as an in vitro alternative to animals for safety and efficacy testing of chemicals and drugs. Based on the concepts developed for these in vitro innervated corneas, hybrid biosynthetic matrices with the proper dimensions, transparency and biomechanical properties for use as corneal replacements in transplantation were also developed. These matrices were successfully implanted into corneas of pigs. Regeneration of corneal tissue and nerves was observed, along with restoration of sensory function. The basic model developed therefore can be used for studying corneal wound healing, nerve-corneal cell interactions and provides a basis for developing corneal replacements for transplantation.
Keywords: Health Sciences, Ophthalmology.